Implementation of High Reliability Organization (HRO) in the Air Traffic Controller (ATC) Profession in Indonesia - Atmaka, Ekky Widha (PT FORMOSA CENDEKIA GLOBAL, 2024)
The ATC profession in Indonesia is a profession that has a high risk and workload, this has also been proven by the establishment of the ATC organization as a High Reliability Organization (HRO). The implementation of HRO is very important to be carried out properly because it has an impact on the performance of ATC personnel which also directly affects flight safety. There are also HRO principles and attributes that have a high standard to run. Therefore, the purpose of this study is to determine the application of HRO to the ATC profession in Indonesia. The method used in this study is a mixed-method, with the category of descriptive analysis and the Miles and Huberman model. The results of the study based on the data analysis test using a Likert Scale, showed the results were Enough with a percentage of 59%. Meanwhile, based on the data analysis test using archives/literature studies, HRO's Goals were produced, in which there were 21 (twenty one) goals/targets.